THE EFFECT OF USING POWERPOINT MEDIA ON STUDENT LEARNING OUTCOMES IN THE MATERIAL ADAPTATION OF LIVING THINGS - Syaepudin Syaepudin; Juhji Juhji (UNIKU PRESS, 2020)
The purpose of this study was to determine the effect of using PowerPoint media on student learning outcomes in the material adaptation of living creatures. The research method uses a quasi-experimental design with a nonequivalent control group design. The study was conducted in classes 6 (six) A and B, each of which numbered 25 students with the same level of homogeneity. Class 6A was chosen as the experimental class and Class 6B as the control class. The sampling technique uses purposive sampling which is to determine the sample based on special characteristics by the expected research objectives. The study was conducted at Bakti Mulya 400 Pondok Indah South Jakarta Elementary School in grade 6. The learning achievement test instrument used multiple-choice questions that had been validated with content and construction. Hypothesis test results through the Independent Samples Test showed a significance value of 2 (two) directions (t-tailed) of 0.002 0.05, so it was concluded that there were significant scores between the control group and the experimental group. These results indicate the influence of the use of PowerPoint media on student learning outcomes in the material adaptation of living things. Although not the only variable that can affect learning outcomes, the use of PowerPoint media by teachers can be an alternative in efforts to increase students' interest and motivation to learn. so that their learning outcomes can improve